First identification of Mycobacterium avium subsp. paratuberculosis in wild ruminants in a zoo in Mexico - A. L. Hernández-Reyes; G. Chávez-Gris; E. Maldonado-Castro; L. E. Alcaraz-Sosa; M. T. Díaz-Negrete (Veterinary World, 2022)
Background and Aim: Paratuberculosis (PTB) is an infectious disease that induces chronic enteritis in ruminants. It is caused by Mycobacterium avium subsp. paratuberculosis (MAP). In this study, we evaluated the presence of MAP using bacteriological, molecular, and anatomopathological studies, based on the clinical suspicion of PTB in a zoo, in an area housing 10 scimitar-horned oryx (Oryx dammah), five giraffes (Giraffa camelopardalis), and three blue wildebeests (Connochaetes taurinus).